Prevalence of Bilirubin Encephalopathy in Calabar, South-South, Nigeria (A 5-Year Review) - Ochigbo, Sunday O.; Venn, Ifeoma; Kingsley, Anachuna (International Journal of Child Health and Nutrition, 2015)
Background: Bilirubin encephalopathy is the clinical syndrome associated with bilirubin toxicity to the central nervous system resulting in chronic and permanent sequelae. It has been estimated that approximately 60% of term babies and 80% of preterm babies develop jaundice within the first week of life. Objective: To determine the prevalence, morbidity and mortality of bilirubin encephalopathy at our centre. Methodology: A retrospective descriptive review of the case files of all babies diagnosed with bilirubin encephalopathy over the past 5 years from January 2010 to December 2014 was undertaken. Information retrieved from the case notes included age, sex, presence of fever, duration of illness, place of delivery, causes and treatment. The outcome measures such as discharged home, discharged against medical advice, and death were also noted. Results: Out of a total of 2,820 babies, 21 (0.74%) were admitted on account of bilirubin encephalopathy. Of these 21, seventeen (81%) were males and four (19%) females giving M; F ratio of 5:1. Eighteen babies (85.7%) had pyrexia, 8(38.1%) and 6(28.6%) were hypertonic and hypotonic respectively on admission. Only 33.3% of the deliveries took place in the health facilities. The established factors responsible for jaundice included infections (septicaemia) (15/71.4%), ABO incompatibility (4/19.1%), and G6PDeficiency (2/9.5%). The mean maximum serum bilirubin of the subjects was 321.3μmol/l (242.5 – 440.3). The case fatality was 4/21(19%). Conclusion: Neonatal septicaemia is associated with bilirubin encephalopathy. Therefore identification and prompt treatment is of utmost importance to avoid morbidity and mortality.